MEMBACA DAN MEMAKNAI RUH KEBERLANJUTAN DALAM ARSITEKTUR VERNAKULAR - Octavia, Linda; Prawoto, Eko (Jurnal Arsitektur Komposisi, 2018)
Abstract: The human view of nature is infinite creating an exploitative attitude like industry towards the natural world and causing chronic damage to nature. Modern humans need to learn more to live in peace with nature and the tradition of society is the entrance to peace with nature. Traditions in modern Indonesian life are somewhat dubious, tend to be interpreted as a loose past and a burden of cultural identity and uselessness. Seeing tradition is basically deeper in finding and identifying true spirits. This paper seeks to find the concept of balance between nature, humans and culture so that humans live in harmony with nature. The thought of vernacular architecture was appointed as a foothold in finding alternative solutions to natural exploitation. Vernacular architecture is expected to answer a big challenge or problem about the sustainability of the earth. This research is a qualitative research by presenting case examples analyzed descriptively using the concept of vernacular architecture as the basis of analysis. As a result, the notion of the spirit of sustainability is in vernacular architecture to protect the preservation of the culture as a whole to reduce the preservation of the earth. Thoughts in vernacular architecture can be a reference for realizing architectural works that value nature and reduce the burden and pressure on nature. Keywords: vernacular architecture, spirit of sustainability, sustainability, traditionAbstrak: Pandangan manusia terhadap alam yang tidak terbatas menimbulkan sikap eksploitatif ala industri terhadap alam dan menimbulkan kerusakan alam yang kronis. Manusia modern perlu belajar lagi untuk hidup berdamai dengan alam dan tradisi masyarakat adalah pintu masuk berdamai dengan alam. Tradisi dalam kehidupan Indonesia modern agak diragukan, cenderung dimaknai sebagai masa lalu yang lepas dan beban identitas budaya serta tidak berguna. Melihat tradisi hakekatnya lebih dalam mencari dan menemukenali ruh yang sejati. Tulisan ini berusaha menemukan konsep keseimbangan antara alam, manusia dan budaya agar manusia hidup harmonis dengan alam. Pemikiran dari arsitektur vernakular diangkat sebagai pijakan menemukan solusi alternatif eksploitasi alam. Arsitektur vernakular diharapkan menjawab tantangan atau permasalahan besar tentang sustainabilitas bumi. Studi ini merupakan kajian kualitatif dengan menyajikan contoh-contoh kasus yang dianalisis secara deskriptif menggunakan konsep arsitektur vernakular sebagai dasar analisis. Hasilnya, pemikiran tentang ruh keberlanjutan ada dalam arsitektur vernakular untuk menjagai keterjagaan budaya secara utuh dalam rangka mengurangi melestarikan bumi. Pemikiran dalam arsitektur vernakular dapat menjadi acuan untuk mewujudkan karya arsitektur yang menghargai alam dan mengurangi beban serta tekanan terhadap alam.Kata Kunci: arsitektur vernakular, ruh keberlanjutan, sustainabilitas, tradisi